Why Capital Hires Labor: A Bargaining Perspective - Dow, Gregory K. (American Economic Review, 1993)
Organizational forms often serve as vehicles for the appropriation of quasi-rent. Capitalist firms typically emerge when production requires noncontractible investments in specific physical assets, because worker control would divert quasi-rents away from asset owners ex post. Conversely, labor-managed firms tend to emerge in niches requiring specialized human capital but general-purpose physical assets. A key result is that capitalist firms can persist in competitive markets even when labor-managed firms would yield a larger total surplus.